Estimation of 200m record from 100m record with consideration of a swimmer's speciality in freestyle swimming race - Nomura, T.; Wakayoshi, K.; Okuno, K. (Biomechanics and Medicine in Swimming VIII, 1999)
The purpose of this study was to estimate the 200m record from the lOOm record with consideration of the swimmer's specialty in freestyle swimming race. The subjects were 127 male and 105 female Japanese national-level swimmers. The subjects were classified under three swimmer's specialties, which were composed of a sprint type (SP), a balanced type (BL) and an endurance type (EN). The multiple regression equation that estimated the 200m record for practical use was as follows: Males, 200m record [sec] = 2*100m record [sec] + 1.707*type + 9.890; Females, 200m record [sec] = 2*100m record [sec]+ 1.719*type + 8.872, where "type" shows SP = 1, BL = 0 and EN= -1. The 200m records were more accurately estimated from the lOOm record, with consideration of the swimmer's specialty than was a simple estimation from the 1 OOm record.